2016
DOI: 10.1097/01.jhq.0000462680.47759.53
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Delays for Patients Requiring In-Hospital Guardianship

Abstract: Nonclinical discharge delays for guardianship patients are costly and potentially unavoidable. Further exploration into policy change is therefore recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The results of this study reflect the Massachusetts’ experience, with no public guardianship program or hierarchy statute. That being said, while this presumably causes the need for more guardianships in Massachusetts, the mechanisms for guardianship are broadly similar nationwide and are likely to result in excessive length of stay and cost similar to those in our population, as demonstrated in studies from other states 7,15‐17 …”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The results of this study reflect the Massachusetts’ experience, with no public guardianship program or hierarchy statute. That being said, while this presumably causes the need for more guardianships in Massachusetts, the mechanisms for guardianship are broadly similar nationwide and are likely to result in excessive length of stay and cost similar to those in our population, as demonstrated in studies from other states 7,15‐17 …”
Section: Discussionmentioning
confidence: 69%
“…To our knowledge, this is among the first studies to investigate healthcare costs and harm to the patient in the form of hospital‐associated complications as a result of guardianship proceedings. Other studies 15,16 have also demonstrated excessive length of stay attributed to nonclinical factors such as guardianship, though they did not quantify the excess stay or compare guardianship cases with a matched control. One study 17 demonstrated total charges of $150,000 per patient requiring guardianship, which are similar to our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies explore the burden of excess days in a single AMC. 20 , 21 These studies find that the burden to the hospital is significant and that the individual is at a heightened risk for secondary infections. However, AMC’s are not representative of the entire hospital system.…”
Section: Discussionmentioning
confidence: 99%
“…However, causes of excess days that could be identified ranged from suboptimal post-acute care bed availability, application processing time for admission to post-acute care facilities, time for evaluation by post-acute care facilities, facility denial and reapplication to another facility, issues in financing medication costs (e.g., chemotherapy, multiple sclerosis disease-modifying therapy), insurance processing and approval, insurance denials, and obstacles related to guardianship status. 25 Developing a better understanding and wider recognition of these issues is needed to improve patient flow and quality of care, and is an area in need of future research to improve quality of care.…”
Section: Discussionmentioning
confidence: 99%